Pharmacokinetics and Nephrotoxicity of Polymyxin MRX-8 in Rats: A Novel Agent against Resistant Gram-Negative Bacteria - Xingyi Qu; Chenxue Guo; Shaojun Liu; Xin Li; Lin Xi; Xiaofen Liu; Jing Zhang (MDPI AG, 2024)
MRX-8 is a novel polymyxin for carbapenem-resistant Gram-negative infections that has been recently evaluated in Phase I clinical trials. Herein, its pharmacokinetics (PK) and nephrotoxicity in rats are reported for the first time. This study aimed at pre-clinical PK and safety assessments. An LC-MS/MS method was developed to determine concentrations of MRX-8 and its major deacylation metabolite, MRX-8039, in rat plasma. Animals were administered a single dose of MRX-8 (2, 4, 6, and 8 mg/kg) or comparator polymyxin B (PMB) (4 and 8 mg/kg) to compare the kidney injury known for the polymyxin drug class. Nephrotoxicity was evaluated using serum creatinine, blood urea nitrogen (BUN) biomarkers, and renal histopathology. In rats, MRX-8 displayed linear PK within the range of 2-8 mg/kg, with approximately 4% of MRX-8 converted to MRX-8039. MRX-8 induced only mild increases in serum creatinine and BUN levels, with an apparent decrease in nephrotoxicity within 24 h, in contrast to PMB, which exhibited a significant and more persistent toxicity. Additional nephrotoxicity biomarkers (plasma NGAL and urinary NGAL, KIM-1, and TIMP-1) have confirmed attenuated MRX-8 kidney injury. Histopathology has revealed significantly greater cellular/tissue toxicity for PMB as compared to MRX-8 (variances of p = 0.008 and p = 0.048 vs. saline control, respectively). Thus, MRX-8 induces a mild and reversible kidney injury in rats compared to PMB. These data support a continued evaluation of the novel polymyxin in human trials.